ANALISIS KEBUTUHAN ESP DI ERA ECONOMI 4.0 BAGI MAHASISWA AKUNTANSI UNIVERSITAS TANJUNGPURA - Regina Septiany Hildegardis; Yohanes Gatot Sutapa Yuliana (ELT in Focus, 2024)
The purpose of this study is to identify the English for Specific Purposes (ESP) needs of accounting students in the Economy and Business program at Tanjungpura University. A sample of sixty-four students (N=64) participated in this study. The quantitative data were obtained through a descriptive statistics analysis of a questionnaire, and the qualitative data were collected from an interview related to the perceptions of the students’ needs. The findings revealed that the current English course for these accounting students is not well-contextualized to their field of study. It should focus more on developing English speaking and listening skills to better prepare students for their future careers, especially in the Economy 4.0 era, where they will encounter global opportunities. This underscores the importance of conducting a need analysis, which is a fundamental step in the ESP field.